Tetraspanins CD81 and CD82 facilitate α4β1-mediated adhesion of human erythroblasts to vascular cell adhesion molecule-1. - Frances A Spring; Rebecca E Griffiths; Tosti J Mankelow; Christopher Agnew; Stephen F Parsons; Joel A Chasis; David J Anstee (PLoS ONE)
The proliferation and terminal differentiation of erythroid progenitors occurs in human bone marrow within erythroblastic islands, specialised structures consisting of a central macrophage surrounded by developing erythroid cells. Many cell-cell and cell-matrix adhesive interactions maintain and regulate the co-ordinated daily production of reticulocytes. Erythroid cells express only one integrin, α4β1, throughout differentiation, and its interactions with both macrophage Vascular Cell Adhesion Molecule-1 and with extracellular matrix fibronectin are critical for erythropoiesis. We observed that proerythroblasts expressed a broad tetraspanin phenotype, and investigated whether any tetraspanin could modulate integrin function. A specific association between α4β1 and CD81, CD82 and CD151 was demonstrated by confocal microscopy and co-immune precipitation. We observed that antibodies to CD81 and CD82 augmented adhesion of proerythroblasts to Vascular Cell Adhesion Molecule-1 but not to the fibronectin spliceoforms FnIII12-IIICS-15 and FnIII12-15. In contrast, different anti-CD151 antibodies augmented or inhibited adhesion of proerythroblasts to Vascular Cell Adhesion Molecule-1 and the fibronectin spliceoform FnIII12-IIICS-15 but not to FnIII12-15. These results strongly suggest that tetraspanins have a functional role in terminal erythropoiesis by modulating interactions of erythroblast α4β1 with both macrophages and extracellular matrix.